2000
DOI: 10.1209/epl/i2000-00403-3
|View full text |Cite
|
Sign up to set email alerts
|

Confining strings in the Abelian-projected SU (3)-gluodynamics

Abstract: Abstract. -String representation of the Wilson loop in 3D Abelian-projected SU (3)-gluodynamics is constructed in the approximation that Abelian-projected monopoles form a gas. Such an assumption is much weaker than the standard one, demanding the monopole condensation. It is demonstrated that the summation over world sheets, bounded by the contour of the Wilson loop, is realized by the summation over branches of a certain effective multivalued potential of the monopole densities. Finally, by virtue of the so-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…. Note that this formula is valid also for the standard case N = 2 and reproduces the SU (3)-result of the compact-QED limit [ 16], [ 13] m 2 D = 3g 2 m ζ. The new parameter of the cumulant expansion,ζI (3) N (N − 1), will be exponentially small provided that at x ∼ 1/2,…”
Section: Properties Of the Su (N )-Casesupporting
confidence: 71%
“…. Note that this formula is valid also for the standard case N = 2 and reproduces the SU (3)-result of the compact-QED limit [ 16], [ 13] m 2 D = 3g 2 m ζ. The new parameter of the cumulant expansion,ζI (3) N (N − 1), will be exponentially small provided that at x ∼ 1/2,…”
Section: Properties Of the Su (N )-Casesupporting
confidence: 71%
“…Such calculations have been initially performed in various Abelian models, where confinement is provided by the monopole condensation. Those include the 3D Georgi-Glashow model and the 4D compact QED [116,117], as well as the 4D dual Abelian Higgs model in the London limit and its [U (1)] N−1 -symmetric generalization [118][119][120][121][122]. In this way, it has been explicitly shown that the vacuum correlation lengths in all these models are equal to the inverse masses of the corresponding dual vector bosons.…”
Section: Correlation Lengths Of the Stochastic Yang-mills Fieldsmentioning
confidence: 99%
“…The string representation of the compact-QED limit has been studied for the SU(3)-case in ref. [11] both in 3D and 4D. Here, similarly to all the above-mentioned papers, we have assumed that W bosons corresponding to different root vectors have the same masses.…”
Section: Su(n)-casementioning
confidence: 99%